2018
DOI: 10.1186/s41938-018-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and identification of the Egyptian wasps (Hymenoptera: Vespidae) based on COI mitochondrial gene sequences

Abstract: The Hymenoptera is one of the vital and biggest insect orders comprising the bees, wasps, sawflies, and ants. Wasps are important to natural and biological pest control because they are predators or parasitoids of pest arthropods. This study investigated the genetic diversity among the three wasps, Vespa orientalis Linnaeus, Polistes bucharensis Erichson, and Polistes mongolicus du Buysson, collected from three different governorates in Egypt, using cytochrome oxidase subunit I (COI) DNA barcoding. PCR was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Thereinto, Consortium for the Barcode of Life (CBOL) initiated scientific research activities using COI for species identification on a global scale, and the data showed that the COI sequences of most species exhibited low intraspecific genetic differences and relatively high interspecific genetic differences (Schindel et al 2005;Ratnasingham et al 2007;CBOL Plant Working Group 2009). Research data in recent years have also reflected that the similarity of the same species is above 98%, and the sequence difference between species is greater than 2% ( Hebert et al 2010;Zhang et al 2011;Schmid-Egger et al 2017;Abd-El-Samie et al 2018;Halim et al 2018;Fernandez-Triana et al 2019). So, in our work, the intraspecific and interspecific differences of COI between A. diffinis and A. radiatum are analyzed.…”
Section: Introductionmentioning
confidence: 87%
“…Thereinto, Consortium for the Barcode of Life (CBOL) initiated scientific research activities using COI for species identification on a global scale, and the data showed that the COI sequences of most species exhibited low intraspecific genetic differences and relatively high interspecific genetic differences (Schindel et al 2005;Ratnasingham et al 2007;CBOL Plant Working Group 2009). Research data in recent years have also reflected that the similarity of the same species is above 98%, and the sequence difference between species is greater than 2% ( Hebert et al 2010;Zhang et al 2011;Schmid-Egger et al 2017;Abd-El-Samie et al 2018;Halim et al 2018;Fernandez-Triana et al 2019). So, in our work, the intraspecific and interspecific differences of COI between A. diffinis and A. radiatum are analyzed.…”
Section: Introductionmentioning
confidence: 87%
“…There is much evidence from the literature which supports the use of molecular markers for species identification and phylogenetic studies. The successful use of molecular markers especially COI for the identification and delimitation of the species was seen in Vespa species identification, Trissolcus species identification, new species of Zaischnopsis, trichogrammatids, hymenopteran parasitoids, and Egyptian wasps are some of the examples from the literature [35][36][37][38][39][40][41] . The molecular data has also been found to be useful for species delimitation as depicted by the studies of Chen and coworkers; Parslow and associates; Benavides and associates and Siddiqui and coworkers [42][43][44][45] .…”
Section: Molecular Characterisationmentioning
confidence: 99%
“…The vespid wasps comprise over 5000 species, including both solitary and social species; these insects are thought to provide important ecosystem services as pollinators of agricultural crops (Hunt et al 1991;Brodmann et al 2008;Mello et al 2011) and natural enemies and regulators of natural arthropod populations and crop pests in agroecosystems (Abd-El-Samie et al 2018;Prezoto et al 2019;Southon et al 2019). However, their impact is largely unstudied, even though they are highly speciose, diverse in form, and distributed worldwide (Nguyen 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular sequence data complement the use of morphological data in species identification, but sometimes molecular data remain the only reliable method for rapid identification of species as they accurately capture the differences among species (Bezeng et al 2017). The COI gene is effective in identification of animal specimens (Hebert et al 2003) though with some exceptions (Gibbs 2018), and has been employed extensively in species identification including vespid wasps (Neumeyer et al 2014;Schmid-Egger et al 2017;Abd-El-Samie et al 2018).…”
Section: Introductionmentioning
confidence: 99%